The perception of rural smallholders on the role of tote officers as agricultural extension agents in enhancing cocoa productivity in the East Coast Region of Sabah - Noviatin Syarifuddin,; Jasmin Arif Shah,; Asnarulkhadi Abu Samah,; Nik Ahmad Sufian Burhan, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The effectiveness of agricultural productivity improvement programs depends on the acceptance of smallholder farmers as the beneficiaries of these programs. However, differences in values, social norms, and traditional farming practices between smallholders and the guidance provided by ToTE officers as agricultural extension agents may hinder the efforts of the Malaysian Cocoa Board to sustain cocoa productivity. Furthermore, cocoa remains the second most important commodity in Sabah's agricultural economy. Therefore, this study aims to investigate the perceptions of rural smallholders regarding the role of ToTE officers as agricultural extension agents in sustaining cocoa productivity. The research strategy employs a realist ontological approach and a positivist epistemological approach to statistically justify smallholder perceptions of ToTE officers. A quantitative case study design using a survey questionnaire was conducted with 195 smallholders, selected through a census sampling method in the districts of the East Coast Zone of Sabah. The findings show that most rural smallholders agree that ToTE officers play a significant role as change agents (mean 4.43). Additionally, the role of ToTE officers as problem solvers and process facilitators showed mean values of 4.40 each. Lastly, the role of ToTE officers as resource connectors demonstrated a mean value of 4.39. It is hoped that the findings of this study will provide guidance to policymakers, particularly the Rural Development Policy (RDP), to advance the agricultural sector and cocoa smallholders in alignment with Pillar 1: Economy, Pillar 7: Prosperous Life, and Pillar 10: Development, in accordance with the roles highlighted by community change agents.